Location,time and preference aware restaurant recommendation method - Habib, Md. Ahsan; Rakib, Md. Abdur (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.